1992
DOI: 10.1002/aoc.590060412
|View full text |Cite
|
Sign up to set email alerts
|

Intake of different chemical species of dietary arsenic by the japanese, and their blood and urinary arsenic levels

Abstract: We calculated the intake of each chemical species of dietary arsenic by typical Japanese, and determined urinary and blood levels of each chemical species of arsenic. The mean total arsenic intake by 35 volunteers was 195 f 235 (15.8-1039) pg As day-', composed of 76% trimethylated arsenic (TMA), 17.3% inorganic arsenic (Asi), 5.8% dimethylated arsenic (DMA), and 0.8% monomethylated arsenic (MA): the intake of TMA was the largest of all the measured species. Intake of Asi characteristically and invariably occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 22 publications
(1 reference statement)
1
29
0
Order By: Relevance
“…Although several studies have reported the pharmacokinetics of the arsenic species including the metabolites, these reports have not considered the influence of arsenic derived from seafood. Since the Japanese people ingest a large quantity of seafood, the urinary concentration of arsenic is higher as an ethnic characteristic; meanϭ 130 mg/l (1.7 mM) for the ethnic groups that commonly ingest seafood (like the Japanese) 25,26) and below 10 mg/l (133 nM) for the ethnic groups that ingest little seafood, respectively.…”
Section: Efficacy Of Arsenic Therapymentioning
confidence: 99%
“…Although several studies have reported the pharmacokinetics of the arsenic species including the metabolites, these reports have not considered the influence of arsenic derived from seafood. Since the Japanese people ingest a large quantity of seafood, the urinary concentration of arsenic is higher as an ethnic characteristic; meanϭ 130 mg/l (1.7 mM) for the ethnic groups that commonly ingest seafood (like the Japanese) 25,26) and below 10 mg/l (133 nM) for the ethnic groups that ingest little seafood, respectively.…”
Section: Efficacy Of Arsenic Therapymentioning
confidence: 99%
“…Typical Japanese diets including 20 to 30 g of seaweed can provide 100 to 500 µg of arsenic per day. [25] In volunteers consuming arsenosugar-rich seaweed, urinary dimethylarsenic concentrations increase sharply within a day of exposure. [26][27][28] In seaweed-eating sheep from Orkney Island, Scotland, daily consumption of arsenic from arsenosugars ranges from 45 to 90 mg. Dimethylarsenic is the major arsenic-containing species in urine in these sheep.…”
Section: Arsenosugarsmentioning
confidence: 99%
“…Toxicologists believe that inorganic arsenic is mainly responsible for cancer whereas arsenobetaine or 'fish arsenic' is considered relatively non-toxic (Ryan et al, 2001). A typical Japanese fish-rich diet contributes as much as 195 µg/d arsenic (Yamauchi et al, 1992), whereas an American diet only contributes around 28 µg/d (Ryan et al, 2001). If it is assumed, for the sake of argument, that the Japanese diet, high in fish intake, represents the dietary picture for early man who lived close to the sea, then on the basis of the safe drinking water arsenic intake being 10% of the total dietary intake, the safe arsenic drinking water limit would be around 10 µg/ℓ As for a 2 ℓ per day water intake for an adult, and 195 µg/d As from food intake (Yamauchi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A typical Japanese fish-rich diet contributes as much as 195 µg/d arsenic (Yamauchi et al, 1992), whereas an American diet only contributes around 28 µg/d (Ryan et al, 2001). If it is assumed, for the sake of argument, that the Japanese diet, high in fish intake, represents the dietary picture for early man who lived close to the sea, then on the basis of the safe drinking water arsenic intake being 10% of the total dietary intake, the safe arsenic drinking water limit would be around 10 µg/ℓ As for a 2 ℓ per day water intake for an adult, and 195 µg/d As from food intake (Yamauchi et al, 1992). Now this is exactly at the current WHO (2004) guideline for arsenic, which probably is confirmation that it is a reasonable limit in terms of safety with respect to the total diet.…”
Section: Discussionmentioning
confidence: 99%